Temporal Stability of In-Hospital Mortality in Acute Pancreatitis: A Nine-Year Tertiary Center Cohort Study - Al-Dawoudi, Abdulrahman; Varlamov, Daniil; Dalain, Mujahed; Freimanis, Davis (Acta medica Lituanica, 2026)
Background. Acute pancreatitis (AP) is a leading cause of gastrointestinal hospitalization and remains associated with measurable in-hospital mortality despite advances in supportive care. While earlier decades were characterized by declining mortality, contemporary temporal patterns within mature tertiary-care systems remain uncertain. We aimed to evaluate longitudinal trends in admission volume, demographic characteristics, intensive care unit (ICU) utilization, and crude, age-standardized, and adjusted in-hospital mortality in a tertiary academic center.Materials and Methods. We conducted a retrospective cohort study of consecutive adult hospitalizations with a primary diagnosis of acute pancreatitis at a tertiary referral center between 2016 and 2024. Temporal trends were assessed using linear and logistic regression models. Age-standardized mortality rates were calculated using direct standardization to a fixed reference population. Multivariable logistic regression evaluated the independent association between year of admission and in-hospital mortality, adjusting for age and sex. A prespecified sensitivity analysis excluded ICU admissions. Analyses were limited by the lack of reliably recorded etiologic and standardized severity data within the administrative dataset.Results. A total of 1,981 hospitalizations were included. Overall, in-hospital mortality was 5.0%. Annual admission volume, median age, sex distribution, and ICU utilization showed no significant temporal trends. Crude mortality ranged from 1.8% to 6.5% annually and demonstrated no significant temporal association. Age-standardized mortality likewise showed no significant trend. In multivariable analysis, year of admission was not independently associated with mortality, whereas advancing age was the strongest measured independent predictor, with a 34% increase in odds of death per 10-year increment. Exclusion of ICU admissions yielded consistent findings.Conclusions. In this nine-year tertiary-center cohort, in-hospital mortality for acute pancreatitis was approximately 5% and did not demonstrate a statistically significant temporal change. After adjustment, mortality risk was more strongly associated with age than with calendar year of admission. These findings suggest relative stability within this cohort; however, given the limitations of the study, further research using larger and more detailed datasets is needed to better characterize temporal trends and determinants of mortality.
Keywords: acute pancreatitis; in-hospital mortality; temporal trends; age; epidemiology